Pre-hospital management and patient-related factors affecting access to the surgical care of appendicitis - a survey study - Kirsi Serenella Lastunen; Ari Kalevi Leppäniemi; Panu Juhani Mentula (Taylor & Francis Group, 2024)
Background and aims Long pre-hospital delay substantially increases the likelihood of perforated appendicitis. This study aimed to find patient-related factors affecting this delay.Methods A survey was conducted for patients with acute appendicitis after appendectomy. The participants were asked about their path to the surgical center and socioeconomic status. Variables affecting delays and the rate of complicated appendicitis were analyzed.Results The study included 510 patients; 157 (31%) had complicated appendicitis with a median prehospital delay of 42 h. In patients with uncomplicated appendicitis, the delay was 21 h, p < .001. Forty-six (29%) patients with complicated appendicitis were not referred to the hospital after the first doctor's visit. The multivariate analysis discovered factors associated with long pre-hospital delay: age 40-64 years (OR 1.63 (95% CI 1.06-2.52); compared to age 18-39), age more than 64 years (OR 2.84 (95% CI 1.18-6.80); compared to age 18-39), loss of appetite (OR 2.86 (95% CI 1.64-4.98)), fever (OR 1.66 (95% CI 1.08-2.57)), non-referral by helpline nurse (OR 2.02 (95% CI 1.15-3.53)) and non-referral at first doctors visit (OR 2.16 (95% CI 1.32-3.53)). Age 40-64 years (OR 2.41 (95% CI 1.50-3.88)), age more than 64 years (OR 8.79 (95% CI 2.19-35.36)), fever (OR 1.83 (95% CI 1.15-2.89)) and non-referral at first doctors visit (OR 1.90 (95% CI 1.14-3.14)) were also risk factors for complicated appendicitis.Conclusions Advanced age, fever and failure to suspect acute appendicitis in primary care are associated with prolonged pre-hospital delay and complicated appendicitis.